Serum Selenium Levels in Patients with Remission and Relapse of Graves' Disease - Wertenbruch, Tina; Willenberg, Holger S.; Sagert, Cornelia; Nguyen, Thi-Bang-Tam; Bahlo, Maryam; Feldkamp, Joachim; Groeger, Claus; Hermsen, Derik; Scherbaum, Werner A.; Schott, Matthias (Medicinal Chemistry, 2007)
Objective: Selenium (Se) in the form of selenocysteine is an essential component of the family of the detoxifying enzymes glutathione peroxidase (Gpx) and of the iodothyronine selenodeiodinases that catalyze the extrathyroidal production of tri-iodothyronine (T(3)). Thus, Se deficiency may seriously influence the generation of free radicals, the conversion of thyroxine (T(4)) to T(3) and a thyroidal autoimmune process. The aim of this study was to investigate whether serum Se levels may influence the outcome of Graves' disease (GD). Design And Methods: 83 patients (77 women, 6 men) with active GD were retrospectively analyzed (mean age 40,0 years). Twenty-four GD patients went into remission and were euthyroid during follow-up (median follow-up: 20.1 months), whereas 59 patients did not go into remission or developed relapse over the following 24 months. TSH receptor autoantibodies (TRAb) were measured using the second generation assay on the basis of human TSH receptor. Se levels were determined at the first visit in our outpatient clinic and were correlated with TRAb levels and clinical outcome of these patients. Results: Median TRAb levels in the group of remission were significantly (p<0.0001) lower than TRAb values in the relapse group (2.1 as compared to 8.6 IU/l). By comparing mean serum Se levels in the remission and relapse group no significant differences were seen (73.0 vs. 71.7 ug/l). Detailed analyses of both groups of patients, however, revealed that highest serum Se levels (>120 ug/l) were seen in the remission group, indicating a positive effect of Se levels on the outcome of GD. In addition, we also compared these results with TRAb levels of these patients. We could show that TRAb levels and serum Se values were positively correlated in the relapse group, whereas a negative correlation of both parameters were seen in the remission group, supporting the idea of a positive effect of Se on thyroidal autoimmune process. Conclusion: Our data indicate that high serum Se levels (>120 ug/l) may influence the outcome of GD. This is important, as Se administration trials in GD, which are under discussion need to be performed with Se supplementation at higher dosages than used in autoimmune thyroiditis.
Keywords: remission